Is Mg17Al12 ductile or brittle? A theoretical insight - Jiajia Wang; Lei Niu; Yanglin Zhang; Jianqing Chen; Jinghua Jiang; Dan Song; Baosong Li; Guobing Ying; Jiangbo Cheng; Aibin Ma (Journal of Magnesium and Alloys, 2023)
The Mg17Al12-phase, which is common and important in Mg-Al alloy, has long been regarded as a brittle phase in experiments but theoretical calculations report controversial results. To unravel why theoretical calculations report controversial results and determine whether Mg17Al12 is brittle or ductile, density functional theory calculations on atomic level are performed to investigate mechanic properties of Mg17Al12 without containing alloying elements and without taking the size effect. The results showed that the parameter k-point played critical role in the DFT-based elastic calculations. The convergent G/B ratio of Mg17Al12 was about 0.52, suggesting that the Mg17Al12-phase was theoretically ductile although its ductility was poor. The chemical bonding in Mg17Al12 was the mixture of metallic Mg-Mg bond and covalent Al-Al bond. The advantage of metallic bonding over covalent bonding provided a possible explanation for the ductility of Mg17Al12. Possible reasons for the brittleness of Mg17Al12 in experiments are also discussed.